Occurrence characteristics of outer zone relativistic electron butterfly distribution: A survey of Van Allen Probes REPT measurements - Binbin Ni; Zhengyang Zou; Xinlin Li; Jacob Bortnik; Lun Xie; Xudong Gu (Geophysical Research Letters)
Abstract Using Van Allen Probes Relativistic Electron Proton Telescope (REPT) pitch angle resolved electron flux data from September 2012 to March 2015, we investigate in detail the global occurrence pattern of equatorial (|λ| ≤ 3°) butterfly distribution of outer zone relativistic electrons and its potential correlation with the solar wind dynamic pressure. The statistical results demonstrate that these butterfly distributions occur with the highest occurrence rate ~ 80% at ~ 20–04 magnetic local time (MLT) and L > ~ 5.5 and with the second peak (> ~ 50%) at ~ 11–15 MLT of lower L shells ~ 4.0. They can also extend to L = 3.5 and to other MLT intervals but with the occurrence rates predominantly < ~25%. It is further shown that outer zone relativistic electron butterfly distributions are likely to peak between 58° and 79° for L = 4.0 and 5.0 and between 37° and 58° for L = 6.0, regardless of the level of solar wind dynamic pressure. Relativistic electron butterfly distributions at L = 4.0 also exhibit a pronounced day‐night asymmetry in response to the Pdyn variations. Compared to the significant L shell and MLT dependence of the global occurrence pattern, outer zone relativistic electron butterfly distributions show much less but still discernable sensitivity to Pdyn, geomagnetic activity level, and electron energy, the full understanding of which requires future attempts of detailed simulations that combine and differentiate underlying physical mechanisms of the geomagnetic field asymmetry and scattering by various magnetospheric waves.